Interactive effect of transplanting time and crop phenology on incidence of brown planthopper and spider population in rice (Oryza sativa) - PADALA, VINOD K; S, RAJNA; N, VENKATESH Y; CHANDER, SUBHASH (The Indian Journal of Agricultural Sciences, 2024)
Brown planthopper (BPH), Nilaparvata lugens (Stal 1854) is a destructive insect pest causing severe yield loss every year in rice (Oryza sativa L.) crop. An experiment was conducted during during kharif (rainy) seasons of 2021 and 2022 at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi to study the effect of transplanting time and crop phenology on brown planthopper (BPH) incidence and spider population in rice. BPH and spider populations were recorded at different phenological stages in early, normal and late transplanted rice. Results showed that a significantly higher mean BPH population was observed in late transplanting in 2021 [54.00±5.31 per hill (nymphs and adults)] and 2022 (40.40±2.62 per hill) compared to normal and early tranplanting. Peak BPH population was observed at the heading (225.60±18.83 per hill) and milking stage (131.00±8.30 per hill) of late transplanted rice in 2021 and 2022, respectively. Likewise, more mean spider population was observed in late transplanting [1.87±0.11 per hill (adults) in 2021 and 2.38±0.08 per hill in 2022]. Two-way ANOVA showed a statistically significant interaction between transplanting time and crop phenology with regard to BPH incidence and spider population in both the years. The highest grain yield was recorded in early transplanted rice (36.08±0.75 q/ha; 35.06±0.49 q/ha) followed by normal (27.53±0.80 q/ha; 28.22±0.75 q/ha) and late transplanted rice crop (17.43±0.82 q/ha; 19.37±0.67 q/ha) respectively during two years. The early transplanted rice crop escaped the peak BPH incidence resulted in increased grain yield. The study demonstrated that both transplanting time and crop phenology influenced the BPH and spider populations.